Microbial Diversity in the Early In Vivo-Formed Dental Biofilm - Heller, D. (Appl Environ Microbiol, 2016)
Although the mature dental biofilm composition is well studied, there is very little information on the earliest phase of in vivo tooth colonization. Progress in dental biofilm collection methodologies and techniques of large-scale microbial identification have made new studies in this field of oral biology feasible. The aim of this study was to characterize the temporal changes and diversity of the cultivable and noncultivable microbes in the early dental biofilm. Samples of early dental biofilm were collected from 11 healthy subjects at 0, 2, 4, and 6 h after removal of plaque and pellicle from tooth surfaces. With the semiquantitative Human Oral Microbiome Identification Microarray (HOMIM) technique, which is based on 16S rRNA sequence hybridizations, plaque samples were analyzed with the currently available 407 HOMIM microbial probes. This led to the identification of at least 92 species, with streptococci being the most abundant bacteria across all time points in all subjects. High-frequency detection was also made with Haemophilus parainfluenzae, Gemella haemolysans, Slackia exigua, and Rothia species. Abundance changes over time were noted for Streptococcus anginosus and Streptococcus intermedius (P = 0.02), Streptococcus mitis bv. 2 (P = 0.0002), Streptococcus oralis (P = 0.0002), Streptococcus cluster I (P = 0.003), G. haemolysans (P = 0.0005), and Stenotrophomonas maltophilia (P = 0.02). Among the currently uncultivable microbiota, eight phylotypes were detected in the early stages of biofilm formation, one belonging to the candidate bacterial division TM7, which has attracted attention due to its potential association with periodontal disease.